A Second Chance to Develop the Human Capital of Out-of-School Youth and Adults : The Philippines Alternative Learning System - World Bank Group (World Bank, Washington, DC, 2018)
Worldwide, approximately 781 million adults are unable to read or write in any language. While adult literacy rates have increased significantly over the past several decades, recent progress largely reflects a more-educated younger generation replacing a less-education older generation. The Philippines has made remarkable progress in improving its public basic education system over the past decade, yet half of Filipino students fail to complete the full cycle of basic education. While lowering the dropout rate is a top priority of the Philippine Department of Education (DepEd), much can be done to improve the educational and employment prospects of those who have already dropped out. For the past five decades, DepEd has operated parallel education systems for youth and adults who did not complete basic formal education. The current incarnation of the Alternative Learning System (ALS) includes two core components, the Basic Literacy Program and the Accreditation and Equivalency (A and E) Programs. Obtaining this credential enables ALS participants to apply to higher education and training institutions or to jobs that require a high school education. In partnership with DepEd, the World Bank conducted a series of assessments of the ALS designed to shed light on the obstacles it faces and assist the government in developing a strategy to address them.This policy note summarizes the empirical evidence obtained from these assessments and other program data and presents policy options to increase the effectiveness of the ALS. This policy note is divided into six sections. Following the introduction,the second section describes the ALS and its target population. The third section examines demand-side challenges and identifies strategies for supporting ALS participants. The fourth section considers supply-side challenges and outlines priorities for strengthening the implementation of the ALS. The fifth section evaluates the returns generated by the ALS, and the sixth section recommends policies to expand its scope and enhance its impact.